Gendered Vulnerabilities and Policy Gaps: Analyzing Alienation Among Indonesian Migrant Women Workers in Malaysia - Kosat, Emanuel; Boro, Veronika Ina Assan; Hurek, Urbanus Ola; Li, Dominggus Elcid; Fauth, Peter (Universitas Teuku Umar, 2024)
Research on women migrant workers in East Nusa Tenggara intends to explore the dimensions of women's vulnerability that are often placed as disciplinary objects in the context and policies of labor migration. This research is described in the discourse of public policy confrontation with the moment of exploitation of women migrant workers in East Nusa Tenggara in the labor market between Indonesia and Malaysia. Indonesian women migrant workers experience vulnerability from recruitment in the upstream line to the placement location in neighboring Malaysia. Using the analytical tool from the perspective of alienation shows that every public policy scheme is not yet inclusive of the civic dimension. This research is based on the post-positivism paradigm using inductive logical reasoning, which implies the specification of the use of critical methods. The results show that pro-market policy choices marginalize the civic participation of women Indonesian migrant workers in East Nusa Tenggara, while alienating women and their work, women with their employers, and women with their civic identity per se. In summary, the significant number of women workers who are targeted by violence is a sign of moments of objectification, discrimination, and exploitation with gender, class, and even nationality-based identities.